Electron transfer quenching in light adapted and mutant forms of the AppA BLUF domain. (29th January 2015) - Laptenok, Sergey P.; Lukacs, Andras; Brust, Richard; Haigney, Allison; Gil, Agnieszka; Towrie, Michael; Greetham, Gregory M.; Tonge, Peter J.; Meech, Stephen R.
Abstract : The Blue Light Using Flavin (BLUF) domain proteins are an important family of photoreceptors controlling a range of responses in a wide variety of organisms. The details of the primary photochemical mechanism, by which light absorption in the isoalloxazine ring of the flavin is converted into a structure change to form the signalling state of the protein, is unresolved. In this work we apply ultrafast time resolved infra-red (TRIR) spectroscopy to investigate the primary photophysics of the BLUF domain of the protein AppA (AppABLUF ) a light activated antirepressor. Here a number of mutations at Y21 and W104 in AppABLUF are investigated. The Y21 mutants are known to be photoinactive, while W104 mutants show the characteristic spectral red-shift associated with BLUF domain activity. Using TRIR we observed separately the decay of the excited state and the recovery of the ground state. In both cases the kinetics are found to be non-single exponential for all the proteins studied, suggesting a range of ground state structures. In the Y21 mutants an intermediate state was also observed, assigned to formation of the radical of the isoalloxazine (flavin) ring. The electron donor is the W104 residue. In contrast, no radical intermediates were detected in the studies of the photoactive dark adapted proteins, dAppABLUF and the dW104 mutants, suggesting a structure change in the Y21 mutants which favours W104 to isoalloxazine electron transfer. In contrast, in the light adapted form of the proteins (lAppABLUF, lW104) a radical intermediate was detected and the kinetics were greatly accelerated. In this case the electron donor was Y21 and major structural changes are associated with the enhanced quenching. In AppABLUF and the seven mutants studied radical intermediates are readily observed by TRIR spectroscopy, but there is no correlation with photoactivity. This suggests that if a charge separated state has a role in the BLUF photocycle it is only as a very short lived intermediate.